Bad gateway - Hanselmann, Simon 1981- (Fantagraphics Books, Inc., 2019)
"Perpetually drunk and high, lovable degenerates Megg and Mogg have drifted through a life full of raucous antics and free of consequences. But their heavy drug use, once a gateway to adventure, has begun to take a grim psychological toll. As her unstable lifestyle finally catches up to her, Megg must turn to her past to uncover the roots of her self-destructive habits that have led her down this dark path."--Amazon
Titel vom Cover
Keywords: Hanselmann, Simon -- 1981-; Witches / Comic books, strips, etc / Fiction; Cats / Comic books, strips, etc / Fiction; Owls / Comic books, strips, etc / Fiction; Werewolves / Comic books, strips, etc / Fiction; Drug addicts / Comic books, strips, etc / Fiction; Depressed persons / Comic books, strips, etc / Fiction; Fantasy comics; Graphic novels; Comic